2018
DOI: 10.1002/cctc.201800486
|View full text |Cite
|
Sign up to set email alerts
|

The Rhodium Catalysed Direct Conversion of Phenols to Primary Cyclohexylamines

Abstract: Cyclohexylamines are important intermediates in chemical industry, which are currently produced from petrochemical sources. Phenols, however, are an attractive sustainable feedstock. We here demonstrate the transformation of phenols with ammonia to primary cyclohexylamines. In contrast to previously reported chemistry which used palladium catalysts, we here show that rhodium is an excellent catalyst for the formation of primary cyclohexylamines. Different parameters were studied and it was shown that the react… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 25 publications
0
28
0
Order By: Relevance
“…Reaction conditions based on our previous work were employed. 26,27 While Ni supported on Nb2O5 gave no activity at all (10 mol% Ni, toluene, 3 h at 160 °C, 4 bar H2 and 0.5 bar NH3; entry 1), all other catalysts formed cyclohexylamine (3a) with a very high selectivity (≥ 90%) and with cyclohexanol as the only significant by-product, regardless of the supporting material. The conversion of phenol, however, varied considerably with the choice of the support.…”
Section: Catalyst and Solvent Screeningmentioning
confidence: 99%
See 1 more Smart Citation
“…Reaction conditions based on our previous work were employed. 26,27 While Ni supported on Nb2O5 gave no activity at all (10 mol% Ni, toluene, 3 h at 160 °C, 4 bar H2 and 0.5 bar NH3; entry 1), all other catalysts formed cyclohexylamine (3a) with a very high selectivity (≥ 90%) and with cyclohexanol as the only significant by-product, regardless of the supporting material. The conversion of phenol, however, varied considerably with the choice of the support.…”
Section: Catalyst and Solvent Screeningmentioning
confidence: 99%
“…In spite of this, the production of primary cyclohexylamines and anilines from phenol remained a difficult challenge until our group reported that these compounds could be efficiently produced by employing a commercial Rh or Pd/C catalyst, respectively, in the presence of H2 and NH3 without the use of any additives. 26,27 More recently, hydrazine was suggested as both the amine and hydride source. 28 So far, no protocols relate to the substitution of these precious metals by more earthabundant metals such as Ni, even though the use of this metal is well established in the chemical industry.…”
Section: Introductionmentioning
confidence: 99%
“…Preferably, the trans-isomer is formed (entries 10, 21, 29). For branched substrate molecules a clear drop in catalytic activity was observed (entries 8,[11][12][13][14][15][16][17][18][19]. These more bulky molecules are sterically hindered and require a longer reaction time.…”
Section: Substrate Scope Investigationmentioning
confidence: 99%
“…1,4 While in the past the starting compounds were often oil-based, progress has been made in recent years in producing amines from bio-based compounds like alcohols, ketones, aldehydes and amino acids. [5][6][7][8][9][10][11][12][13][14][15][16][17] While these methods are very successful, reductive amination of carboxylic acids could be a desirable complementary method for sustainable amine synthesis.…”
Section: Introductionmentioning
confidence: 99%
“…Apart from anilines, the synthesis of cyclohexane amines by the direct amination‐hydrogenation of phenols is also of central importance because cyclohexylamine‐based products serves as key intermediate and building block in organic synthesis and drug discovery [34] . In this respect, De Vos and co‐workers successfully demonstrated the selective transformation of lignin‐derived phenols with ammonia to primary cyclohexylamines in presence of commercially available Rh/C catalyst under mild conditions [35a] . Among various tested solvents, isopropanol was found to be the best due to its protic nature.…”
Section: Synthesis Of Amines From Lignin‐derived Monomersmentioning
confidence: 99%